Problem-Based Learning a Vehicle to Teach Critical Thinking, Reading the Scientific Literature - Teresa Marshall; Michael Finkelstein; Marsha Cunningham-ford (Association of American Medical Colleges, 2010)
Abstract Introduction This module presents a problem-based learning (PBL) curriculum designed to introduce first-year dental students to the concepts of critical thinking, scientific literature, and evidence-based dentistry. Four cases are scheduled throughout the year, with each case targeting a specific content area and building in complexity. Targeted content areas include a dental/scientific controversy; dental ethics; caries and periodontal disease; and systemic and oral relationships. Methods This resource includes course organization materials, the cases, facilitator notes for training purposes, and lecture content. Each case includes a resource assignment, a learning report, and an exam. Each first-year dental student class of 80 students is divided into 10 groups of eight students; group assignments are switched after case two. Facilitators are not required to have expertise in any dental specialty. Resource assignments, learning reports, and exams are evaluated by the course directors to ensure consistent student feedback. Results This curriculum has resulted in significant improvement in student performance. Current first-year dental students are reading the scientific literature at an expected, novice level. Discussion This PBL curriculum has evolved in response to student feedback, faculty concerns, growth in evidence-based science, and emphasis on lifelong learning. Reading scientific literature is a fundamental component of lifelong learning and professional practice. As such, we present this full PBL curriculum as a model for other institutions to consider.